1969
DOI: 10.1007/bf01476786
|View full text |Cite
|
Sign up to set email alerts
|

Laser Q-switching by organic solvents

Abstract: The role of the solvent in the passive Q-switching of lasers by solutions of organic dyes has been examined in detail. It was found that several pure organic solvents could themselves partially Q-switch the laser, in the absence of the dye. This behaviour was observed for both ruby and neodymium : glass lasers. Pulse-widths as short as 20 nsec were occasionally recorded. Peak powers up to 2 MW have been observed using 1-chloronaphthalene to switch a ruby laser. It is proposed that Q-switching arises from an en… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1969
1969
1986
1986

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Recently it has been demonstrated that pure organic solvents are able to cause pulse sharpening of a spiking laser by the formation of a stationary periodic modulation of the refractive index [15]. It was reported in that experiment that no pulse sharpening was observed when carbon disulphide was placed in the resonator of a ruby laser.…”
Section: P U L S E S T R E T C H I N G Of Q -S W I T C H E D L a S E R Smentioning
confidence: 99%
“…Recently it has been demonstrated that pure organic solvents are able to cause pulse sharpening of a spiking laser by the formation of a stationary periodic modulation of the refractive index [15]. It was reported in that experiment that no pulse sharpening was observed when carbon disulphide was placed in the resonator of a ruby laser.…”
Section: P U L S E S T R E T C H I N G Of Q -S W I T C H E D L a S E R Smentioning
confidence: 99%